The effect of changing resistors training on developing some functional and physical indicators for runners - Chaleefah, Rafaa Rashid; Hilal, Saeed Alwan (International Journal of Psychosocial Rehabilitation, 2020)
This section has been included to get acquainted with the research, as it contained the introduction in which the researcher addressed the need to use new types of modern training methods to upgrade athletics and short-distance players in particular and is one of the most important requirements that must be paid attention to in order to develop the levels of these players to the highest possible degree so The researcher was interested in using one of these methods in her study, and this method (variable resistances training), a method that relies on the use of various exercises such as jumping barriers and weightlifting exercises in various forms and with intense stress and a codified training volume in order to know the extent of the impact of these exercises on the development of special strength and some physiological and mechanical aspects and access to Achievement, according to a well-executed kinetic performance and path, in one of the most important short distance races, which is the 200m race. Hence the importance of the research in trying to identify the extent of the effect of using the method of variable resistances such as the use of weightlifting exercises and plyemetric exercises and mixing between these two types of exercises in one method and continuous pregnancy and for a specific period of time on the development of functional, physical and mechanical aspects of the hostile (200 m). The research problem came that most of the training curricula did not give the focused importance of studying the effects of this type of differential strength training by scientific methods that depend in its study on the physiological, physical and mechanical aspects. Therefore, the researcher decided to address this problem as a contribution to the possibility of developing an accurate scientific approach and a modest attempt to advance the curricula Training by using variable (differential) resistance exercises in an effective way leads to improving mathematical technique and raising the level of achievement. The objectives of the research, to know the effect of the variable resistance training method in developing the values of some functional, physical and biomechanical variables and achievement for the 200m hostility from the members of the experimental group. Identify the differences in the values of some physical and functional and biomechanical variables and the achievement of the 200m enemy between the pre and post tests of the experimental and control groups. Identify the results of differences in the values of some physical, functional, and biomechanical variables, and accomplish the 200m enemy between the two experimental and control groups in the dimensional tests. The research assumptions included. There are statistically significant differences between the results of physical tests, functional and mechanical indicators, and achievement before and after the use of the variable resistivity training method for members of the experimental group. There are statistically significant differences between pre and post tests in the values of some physical and functional variables and mechanical bio and achievement in the non-200m for the experimental and control groups. There are statistically significant differences between the experimental and control groups in the values of some physical, functional and biomechanical variables and achievement in the enemy of 200 m in the dimensional tests.